CROSS-BORDER TECHNOLOGY TRANSFER IN THE CONTEXT OF TECHNOGLOBALISM - Liutak , O.M.; Kravchuk , P.Ya. (The actual problems of regional economy development, 2025)
The purpose of the study is to analyze the features of cross-border technology transfer in the context of technoglobalism, determine its impact on the development of the global innovation ecosystem and formulate recommendations for optimizing mechanisms for international scientific and technological exchange. The research methodology involves the use of a comprehensive approach, which includes a comparative analysis of the study of the processes of cross-border technology transfer in the context of technoglobalism. To determine the key factors affecting the effectiveness of cross-border technology transfer in the context of technoglobalism, an analysis of factors such as the level of infrastructure, political conditions and legal barriers was conducted. A SWOT analysis matrix of cross-border technology transfer in the context of technoglobalism was constructed, which proved that this process has significant potential for the development of the world economy, but also contains certain risks: inequality in access to technology, legal barriers, dependence on foreign technologies. Recommendations are substantiated for improving policies and strategies for cross-border technology transfer in the context of technoglobalism: development of legal and regulatory infrastructure, stimulation of investments in research and innovation projects, improvement of access to technology for developing countries, improvement of education and skills in the field of innovation and technology, promotion of cooperation between countries and private companies, development of infrastructure for technology transfer. The study of cross-border technology transfer in the context of technoglobalism is of important practical importance for the formation of effective policies in the field of innovation and development of national economies. The results can be used to improve mechanisms for international cooperation and technological exchange between countries: to reduce technological backwardness and accelerate the integration of new technologies into industrial processes. In addition, the study of technology transfer contributes to the creation of favorable conditions for investment and the development of high-tech sectors of the economy.